Columbus Delano family papers - Delano, Columbus, 1809-1896.; Delano, John Sherman
Correspondence (largely 1869) and photograph album relating to Ohio and national politics and patronage, the Republican Party, western lands, railroad expansion, and personal and financial matters. Includes letters concerning the purchase of the archives of the Confederate States of America. Correspondents include Henry Ward Beecher, Simon Cameron, William E. Chandler, Schuyler Colfax, Roscoe Conkling, Shelby M. Cullom, Grenville Mellen Dodge, Hamilton Fish, James A. Garfield, Jay Gould, Ulysses S. Grant, Rutherford Birchard Hayes, Whitelaw Reid, and John Sherman.
Family members include Columbus Delano, U.S. secretary of the interior and representative from Ohio, and his son, John Sherman Delano, businessman.
Collection material in English.
Keywords: Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Cullom, Shelby M. -- 1829-1914 -- Correspondence; Dodge, Grenville Mellen, -- 1831-1916 -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Gould, Jay, -- 1836-1892 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Delano family; Republican Party (U.S. : 1854- ); Land speculation -- West (U.S.); Patronage, Political -- Ohio; Railroads; Confederate States of America -- Archival resources; Ohio -- Politics and government; Cabinet officers; Representatives, U.S. Congress -- Ohio